2018
DOI: 10.18332/tpc/90968
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic correlates of intention to quit smoking for good among U.S. adult menthol and non-menthol smokers: Evidence from the 2013–2014 National Adult Tobacco Survey

Abstract: INTRODUCTION In the U.S. significant progress has been made to reduce cigarette use, yet menthol cigarette use is a continuing public health problem, especially among young adults and Black/African Americans. Smoking cessation is warranted to reduce smoking-related diseases and premature death. Ample evidence has demonstrated that having an intention to quit smoking is strongly associated with attaining cessation. The objective of this study was to identify and compare the sociodemographic correlates of inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…Our study showed that older smokers were more likely to have the intention to quit smoking than those younger smokers. Since age had been identified among positive key predictors for willingness to quit among tobacco users, 9 , 17 our results were in line with these studies. Other studies showed results on the opposite side when older smokers had lower odds of quitting intention than younger ones.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our study showed that older smokers were more likely to have the intention to quit smoking than those younger smokers. Since age had been identified among positive key predictors for willingness to quit among tobacco users, 9 , 17 our results were in line with these studies. Other studies showed results on the opposite side when older smokers had lower odds of quitting intention than younger ones.…”
Section: Discussionsupporting
confidence: 89%
“…This figure was in line with results from India (52.2%) using GATS data to report 9 or results from the U.S (49.5% among males, 50.4% among females) using National data. 17 Since the launch of the Law on Prevention and Control of Tobacco Harms in 2012 by the Vietnamese Congress, 4 many tobacco control initiatives have been implemented, such as: stipulating places where smoking is not allowed, applying health warnings both in text and pictures on cigarette packs, completely ban of tobacco advertising, promotion, and sponsorship, and establishing the VNTCF. So, the increase in intention to quit smoking might be attributed to these tobacco control interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Although the relationship between smoking cessation and socioeconomic factors has been studied in depth in many cultures (21)(22)(23)(24)(25)(26), few studies on the factors affecting the decision to stop smoking have been conducted on Saudi Arabians. Our results showed that several factors were significantly associated with an increased willingness to stop smoking after the tax was imposed.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, among racial/ethnic minorities, lower annual income was associated with greater motivation to quit. Among young adults, being unemployed is associated with greater intention to quit [79], and another study found greater intention to quit among Black Americans compared with White Americans [80]. Despite this, low-income and Black smokers have been found to be less likely to quit than their counterparts [81,82].…”
Section: Discussionmentioning
confidence: 99%